2005
DOI: 10.1002/syn.20154
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine and amphetamine both enhance synaptic transmission in the amygdala–nucleus accumbens pathway but with different time‐courses

Abstract: Excitatory glutamatergic fibers from limbic structures, such as the hippocampus and the basolateral amygdala, are known to converge on the same neurons in the nucleus accumbens. We have recently shown that ketamine, at a dose (25 mg/kg) that produces psychosis-like behaviors in rats, decreases glutamatergic transmission between the hippocampus and the nucleus accumbens. Here we investigated whether ketamine also affects glutamatergic transmission between the basolateral amygdala and the nucleus accumbens. We a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 35 publications
0
9
1
Order By: Relevance
“…It is possible that glutamatergic mechanisms might also participate to the acquisition of latent inhibition. Dysfunction of glutamatergic inputs to the accumbens by ketamine (Hunt et al, 2005;Kessal et al, 2005 and present results) might therefore underlie the disruption of latent inhibition observed with this compound in our conditioned-fear paradigm.…”
Section: Discussionmentioning
confidence: 51%
“…It is possible that glutamatergic mechanisms might also participate to the acquisition of latent inhibition. Dysfunction of glutamatergic inputs to the accumbens by ketamine (Hunt et al, 2005;Kessal et al, 2005 and present results) might therefore underlie the disruption of latent inhibition observed with this compound in our conditioned-fear paradigm.…”
Section: Discussionmentioning
confidence: 51%
“…In contrast, systemic AMPH administration in behaving animals has more heterogeneous effects (Rebec, 1987;Haracz et al, 1993;Kessal et al, 2005). The present study showed that systemic AMPH administration in behaving animals can enhance particular excitatory task-related firing patterns, while leaving others unaffected.…”
Section: Comparison To Other Electrophysiological Studiesmentioning
confidence: 46%
“…An acute, low dose of amphetamine (1.5 mg/kg) has been shown to enhance synaptic transmission between the basolateral amygdala and nucleus accumbens, 30 min after the injection (Kessal et al 2005). Chronic, but not acute, doses of amphetamine (between 1 and 4 mg/kg) have been shown to induce an up-regulation of glial fibrillary acidic protein (GFAP), which is considered a marker of astrogliosis and neurotoxicity, in the rat hippocampus (Frey et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The amygdala, and specifically the basolateral/lateral complex of the amygdala, is involved in encoding an aversive association with both the context and tone (Fanselow and Gale 2003;Fanselow and Poulos 2005). Amphetamine has been shown to alter amygdalar activity in a number of ways, including potentiating the synaptic transmission between the amygdala and nucleus accumbens (Kessal et al 2005). The hippocampus has also been implicated in amphetamine-induced locomotor activity, as lesions of the ventral hippocampus (VH) disrupt amphetamine-induced locomotion, and stimulation enhances it (White et al 2006).…”
Section: Introductionmentioning
confidence: 99%